An Improved Protocol for the Synthesis of α‐Trifluoromethylthio‐Substituted Ketones by Copper‐Mediated Trifluoromethylthiolation of α‐Bromo Ketones. Issue 33 (19th October 2014) - Huang, Yangjie; He, Xing; Li, Haohong; Weng, Zhiqiang
Abstract: An efficient and practical approach to α‐trifluoromethylthio‐substituted ketones was developed. The trifluoromethylthiolation of (bpy)Cu(SCF3 ) (bpy = 2, 2′‐bipyridyl) with various α‐bromo ketones afforded the desired α‐trifluoromethylthio‐substituted ketones in good yields. The reaction tolerates more functionally than previously reported methods and demonstrates efficient scalability and practicality. Abstract : An improved protocol for the copper‐mediated trifluoromethylthiolation of α‐bromo ketones by using (bpy)Cu(SCF3 ) (bpy = 2, 2′‐bipyridyl) to afford the corresponding α‐trifluoromethylthio‐substituted ketones in good to excellent yields is presented. The procedure tolerates electron‐withdrawing and electron‐donating groups on the aromatic rings.